6-gingerol and its derivatives inhibit Helicobacter pylori-induced gastric mucosal inflammation and improve gastrin and somatostatin secretion - Qian, Jiali; Li, Zhennan; Wang, Jinhui; Lin, Yuxian; Yu, Yingcong (Frontiers in Microbiology, 2024)
The resistance of Helicobacter pylori (H. pylori) has increased in recent years, prompting a trend in the research and development of new drugs. In our study, three derivatives (JF-1, JF-2, and JF-3) were synthesized using 6-gingerol as the main component, while JF-4, containing both 6-gingerol and 6-shogaol as the main components, was extracted from dried ginger. The minimum inhibitory concentrations (MICs), determined using the ratio dilution method, were 80 μg/mL for JF-1, 40 μg/mL for JF-2, 30 μg/mL for JF-3, 40 μg/mL for JF-4, 60 μg/mL for 6-gingerol standard (SS), and 0.03 μg/mL for amoxicillin (AMX). After treating H. pylori-infected mice, the inflammation of the gastric mucosa was suppressed. The eradication rate of H. pylori was 16.7% of JF-3 low-dose treatment (LDT), 25.0% of JF-3 high-dose treatment (HDT), 16.7% of JF-4 LDT, 16.7% of JF-4 HDT, 30% of SS LDT, 50% of SS HDT, and 36.4% of the positive control group (PCG). The levels of gastrin, somatostatin (SST), IFN-γ, IL-4, and IL-8 were significantly recovered in the JF-3 and JF-4 administration groups, but the effect was stronger in the high-dose group. These results demonstrate that 6-gingerol and its derivatives have significant anti-Helicobacter pylori effects and are promising potential treatments for H. pylori infection.